(untitled) (Journal of Contemporary Issues in Accounting, 2024)
The Nigerian consumer goods sector is central to the nation’s economy and has contributed not only to the GDP but also to employment. However, economic difficulties such as currency fluctuations, changes in policies, and commodity price changes commonly occur and have contributed to financial distress in firms operating within this sector. This study adopts the Altman Z-Score as the measure in determining the influence of two main firm attributes – leverage and age – on financial distress among listed consumer goods firms in Nigeria. From panel regression analysis of 16 firms for a 12-year period, it is observed that leverage significantly and negatively influences the Altman Z-Score-that is, increased financial distress accrues with increased debt levels. On the other hand, firm age positively influences the Z-Score; this means that the older the firm, the more financial stability is obtained. These results depict the importance of prudent debt management and firm longevity toward improving financial health. This study provides valuable information to industry participants with the intention of alleviating financial distress and improving stability in the consumer goods sector of Nigeria.